2020
DOI: 10.1186/s12974-020-01937-8
|View full text |Cite
|
Sign up to set email alerts
|

CRID3, a blocker of apoptosis associated speck like protein containing a card, ameliorates murine spinal cord injury by improving local immune microenvironment

Abstract: Background: After spinal cord injury (SCI), destructive immune cell subsets are dominant in the local microenvironment, which are the important mechanism of injury. Studies have shown that inflammasomes play an important role in the inflammation following SCI, and apoptosis-associated speck-like protein containing a card (ASC) is the adaptor protein shared by inflammasomes. Therefore, we speculated that inhibiting ASC may improve the local microenvironment of injured spinal cord. Here, CRID3, a blocker of ASC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…SCI-induced inflammation and oxidative stress are highly disordered metabolic processes, mainly manifested as an imbalance of the microenvironment, ultimately leading to injury recovery and progressive tissue degradation [ 15 , 38 , 39 ]. Macrophages play a vital role in tissue repair in the inflammatory microenvironment of SCI, but this process often results in a state where the damaged tissue cannot be repaired due to the change of macrophage polarization direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCI-induced inflammation and oxidative stress are highly disordered metabolic processes, mainly manifested as an imbalance of the microenvironment, ultimately leading to injury recovery and progressive tissue degradation [ 15 , 38 , 39 ]. Macrophages play a vital role in tissue repair in the inflammatory microenvironment of SCI, but this process often results in a state where the damaged tissue cannot be repaired due to the change of macrophage polarization direction.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are one of the first activated inflammatory cells and play an important role in the inflammatory process [ 12 ]. As the predominant effector cells, macrophages enter the injured site and polarize into M1 and M2 type in inflammatory responses [ 15 , 16 ]. Activated M1-type macrophages are characterized by the production of ROS that indicates a rapid and powerful response to trigger inflammation [ 17–19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surviving motor neurons were quantified by counting all such cells in the ventral horn. The three staining methods were described previously ( Chen et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al. demonstrated that a stronger local immune microenvironment inhibited apoptosis, thus aiding recovery in murine SCI ( 24 ). Mohrman et al.…”
Section: The Role Of the Immune Response In Pathophysiological Proces...mentioning
confidence: 99%